HYDROCARBON COMPONENTS IN CARBONACEOUS METEORITES - Kissin Y.V. (My University, 2003)
Currently, the presence of free n-alkanes and isoprenoid alkanes in carbonaceous meteorites is usually explained either by microbial contamination during the period between the meteorite fall and collection or by contamination from the environment of analytical laboratories and museums. The goal of this research was to repeat analysis of hydrocarbon components in meteorites and to investigate possible meteorite contamination routes discussed in the literature. Experimental analysis of free organic constituents in five carbonaceous meteorites by infrared spectroscopy (IR) and gas chromatographic (GC) methods confirmed the presence of extractable aliphatic components, n-alkanes in the C15H32-C27H56 range and isoprenoid alkanes (phytane, pristane, and norpristane), in some of these meteorites. The contents of these compounds vary depending on the source. Insoluble organic components of two meteorites (meteorite kerogens) were isolated, and their composition was analyzed by IR and cracking/GC methods. Comparison with the data on several terrestrial contamination sources proposed in the literature shows that the presence of free saturated hydrocarbons in meteorites and the composition of the meteorite kerogen could not be explained either by microbial contamination or by contamination from the laboratory environment. The types of the hydrocarbons in meteorites resemble those typical of ancient terrestrial deposits of organic-rich sediments, except for the absence of lighter hydrocarbons, which apparently slowly evaporated in space, and multi-ring naphthenic compounds of the biologic origin, steranes, terpanes, etc. The prevailing current explanation for the presence of free linear saturated hydrocarbons in carbonaceous meteorites, apart from contamination, is the abiotic route from hydrogen and carbon monoxide. However, the data on the structure of meteorite kerogens require a search for different routes that initially produce complex polymeric structures containing n-alkyl and isoprenoid chains which are attached, via polar links (esters, salts, etc.), to a cross-linked polymer matrix. Later, the polymer slowly decomposes with the liberation of free aliphatic hydrocarbons.